2016
DOI: 10.18520/cs/v111/i11/1816-1824
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive HPLC Method for Estimation of Total or Individual Curcuminoids in <i>Curcuma</i> Cultivars and Commercial Turmeric Powders

Abstract: The action of turmeric depends on three curcuminoids: curcumin, demethoxycurcumin and bisdemethoxycurcumin, whose distribution is highly varied among cultivars. A sensitive method for estimation of all three curcuminoids is essential for quality control. We developed a HPLC-MS method with lowest limits of detection and quantification of curcuminoids. Mass spectrometry (MS) authenticated the identity of curcuminoids. Principal component analysis of curcuminoids established the high variation among the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In one of our previous studies, we reported that the HPLC method could be a valuable tool to differentiate the cultivars of Curcuma spp. based on their curcuminoids content ratios ( Kulyal et al, 2016 ). Curcuminoids play a significant role in food, cosmetics, and medicinal compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our previous studies, we reported that the HPLC method could be a valuable tool to differentiate the cultivars of Curcuma spp. based on their curcuminoids content ratios ( Kulyal et al, 2016 ). Curcuminoids play a significant role in food, cosmetics, and medicinal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…are dependent on their chemical profiles, studies on the chemical constituents of turmeric/wild turmeric and their essential oils gained significance. Thin-layer chromatography (TLC) is one of the methods employed to quantify curcumin ( Setyaningsih et al, 2016 ) and other curcuminoids ( Phattanawasin et al, 2009 ) in Curcuma longa L. A few different techniques used were HPTLC ( Pathania et al, 2006 ; Paramasivam et al, 2009 ), nuclear magnetic resonance (NMR) spectroscopy ( Li W. et al, 2009 ), and the HPLC method ( Kulyal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kulyal and coworkers applied principal component analysis (PCA) to the characterization of turmeric cultivars. Authors concluded that curcuminoid levels could be used to assess the turmeric quality and to discriminate among the plant varieties [28]. In another study, gas chromatography-MS (GC-MS) and LC-MS platforms were used to obtain the compositional profiles of curcuminoids and terpenoids as the data for PCA and cluster analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled to mass spectrometry (GC–MS) has also been used for the characterization of powdered turmeric [ 32 ] and turmeric oil [ 33 ] samples. Nevertheless, liquid chromatography (LC) with UV detection (LC-UV) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and coupled to mass spectrometry (LC–MS) [ 32 , 41 ] are currently the techniques of choice. Besides, the great chemical diversity among bioactive substances, including polyphenolic and curcuminoid compounds, and the wide range of concentrations in which these phytochemicals can be found in turmeric and related products make liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) the most appropriate strategy for characterization, identification and authentication purposes [ 42 ].…”
Section: Introductionmentioning
confidence: 99%